Apresentação (FR) - Blondeau, Nicole; Potolia , Anthippi; Damasco, Denise Gisele de Britto; Allouache, Ferroudja; Spita, Doina; Pinheiro-Mariz, Josilene (Revista Letras Raras, 2022)
Apresentação (FR).